Low-cost interventions for big impacts in dryland production systems. Issue 9 (29th July 2019) - Chander, Girish; Reddy, Tappari Yellamanda; Kumar, Shalander; Padmalatha, Yadati; Reddy, Sahadeva; Adinarayana, Gurram; Wani, Suhas P.; Reddy, Yerragonda Venkata Malla; Srinivas, Komuravelly
ABSTRACT: A study at selected action sites in semi-arid region of Andhra Pradesh, India, showed widespread land degradation due to low levels of soil organic carbon (78% of fields) and deficiencies of available nutrients like phosphorus (34%), sulfur (93%), calcium (33%), zinc (84%), boron (73%), and copper (33%). Soil test-based addition of deficient micro- and macronutrients increased food grain production by 30–40% and straw (which is used as fodder) production by 10–30%. Micro-watershed scale low-cost cement-lined farm-ponds at smallholder farm level proved a scalable technology for drought-proofing of crops resulting into additional crop yield by more than 30% during 2015. Augmentation of water sources also facilitated farmers' to successfully diversify the production system. Shared machinery resources improved the operational and economic efficiency of farm sowing operations through higher crop yields by around 10%. We conclude that a mix of low-cost critical interventions if out-scaled in a large number of dryland small holdings through policy support may not only improve productivity and livelihoods, but also enhance their abilities to effectively cope with the climatic aberrations.